HUBUNGAN KARAKTERISTIK KELUARGA DENGAN KASUS BALITA GIZI BURUK PADA KELUARGA PETANI KARET DI WILAYAH BINAAN WAHANA VISI INDONESIA AREA DEVELOPMENT PROGRAM KABUPATEN NIAS TAHUN 2013 - Henrika Gulo; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Nutrition have important part in human life cycle. The low Index Of Human Development in Indonesia is influenced by the nutrition status and public health. It can be seen from the high infant mortality rates, and children under five, and also maternal mortality.   This research aims to know the relations between characteristics family with sever malnutrition case of children under five at rubber farmer family in the region's of Wahana Visi Indonesia Area Development Program in Nias in 2013. This research is observational by using case control design. Populations are all children under five, which sever malnutrition and those who not malnutrition in three distric in Kabupaten Nias which is the region’s of WVI ADP NIAS. Data analysis by using chi-square to find Odds Ratio (OR).   The result that there is a meaningful relation between mother’s knowledge with children under five malnutrition cases (p=0,003;OR=9,100), family income with children under five malnutrition (p=0,000;OR=0,037). Variable of mother education and children’s amount in family do not show any meaningful relation with children under five malnutrition cases.   WVI ADP Nias and the health center is expected, especially in Kabupaten Nias to improve health education, counseling about land use in order to maintain the availability of food and provide health counseling, especially to mothers of malnourished children on the importance of keeping nutrition for children stay healthy as well as its effects and consequences when children are not getting enough nutrition.   Keyword : Mother characteristic, family economy social level, children under five nutritional status.